EXPLORING STATE-OF-THE-ART SOFTWARE FOR FORENSIC AUTHORSHIP IDENTIFICATION - Guillén Nieto, Victoria; Vargas Sierra, Chelo; Pardiño Juan, María; Martínez Barco, Patricio; Suárez Cueto, Armando (International Journal of English Studies, 2008)
Back in the 1990s Malcolm Coulthard announced the beginnings of an emerging discipline, forensic linguistics, resulting from the interface of language, crime and the law. Today the courts are more than ever calling on language experts to help in certain types of cases, such as authorship identification, plagiarism, legal interpreting and translation, statement analysis, and voice identification. The application of new technologies to the analysis of questioned texts has greatly facilitated the work of the language scientist as expert witness in the legal setting, and contributed to the successful analysis and interpretation of style providing statistical and measurable data. This article aims at presenting linguists and researchers in forensic linguistics with an exploration of the strengths, limitations and challenges of stateof- the-art software for forensic authorship identification.